ONE HUNDRED YEARS FROM ENCINAS’ INITIATION - Flores Barboza, José Clemente (2014)
In the 20th century there were several innovations in education. The New School had several proposals: create in the child an interest for learning, personalize the education depending on the needs of the student, preservation of freedom, stimulate intellectual interests, affective and moral needs. In Peru, Encinas, a key figure in education, develops admirably these ideas. These are Encinas proposals: learning must be pertinent and useful, the teacher has to assure a meaningful learning, maturation stages have to be taken into account, the teacher must be a leader capable of orienting others